The landscape of heat pump adoption in Canada: a market segments approach - Andrew, Kevin; Pardy, Aaron; Rhodes, Ekaterina (Frontiers in Energy Efficiency, 2024)
Heat pumps are an important technology for reducing residential building emissions, however their adoption rate in North America is far below what is needed to meet emission reduction targets. This paper uses a representative web-based survey of Canadian homeowners (n=3,804) to identify and describe characteristic and attitudinal trends of three market segments of Canadian homeowners: Pioneers (heat pump owners), Potential Early Mainstream buyers (homeowners currently willing to purchase a heat pump), and Late Mainstream buyers (homeowners currently unwilling to purchase a heat pump). We find that personal capability, contextual and attitudinal factors are significant determinants of market segments. For example, being younger, more educated and wealthier is positively associated with market segmentation in Canada. A novel finding is that voting and living in rural areas is strongly associated with willingness to install a heat pump. The Atlantic Provinces, Quebec and British Columbia are all more likely than Ontario and Alberta to adopt heat pumps while the Prairies are less likely. This is true even after controlling for personal capability, contextual and attitudinal variables. We find an important role for contextual variables in explaining the geographical distribution of heat pump market segments.